Ricerca, mediante tecniche di proteomica, di biomarcatori proteici utili nella valutazione della qualità degli alimenti di origine animale - Foschi, Jurgen <1979> (Alma Mater Studiorum - Università di Bologna, 2009)
In the last decades, the increase of industrial activities and of the request for the world food requirement, the intensification of natural resources exploitation, directly connected to pollution, have aroused an increasing interest of the public opinion towards initiatives linked to the regulation of food production, as well to the institution of a modern legislation for the consumer guardianship. This work was planned taking into account some important thematics related to marine environment, collecting and showing the data obtained from the studies made on different marine species of commercial interest (Chamelea gallina, Mytilus edulis, Ostrea edulis, Crassostrea gigas, Salmo salar, Gadus morhua). These studies have evaluated the effects of important physic and chemical parameters variations (temperature, xenobiotics like drugs, hydrocarbons and pesticides) on cells involved in the immune defence (haemocytes) and on some important enzymatic systems involved in xenobiotic biotransformation processes (cytochrome P450 complex) and in the related antioxidant defence processes (Superoxide dismutase, Catalase, Heat Shock Protein), from a biochemical and bimolecular point of view. Oxygen is essential in the biological answer of a living organism. Its consume in the normal cellular breathing physiological processes and foreign substances biotransformation, leads to reactive oxygen species (ROS) formation, potentially toxic and responsible of biological macromolecules damages with consequent pathologies worsening. Such processes can bring to a qualitative alteration of the derived products, but also to a general state of suffering that in the most serious cases can provoke the death of the organism, with important repercussions in economic field, in the output of the breedings, of fishing and of aquaculture. In this study it seemed interesting to apply also alternative methodologies currently in use in the medical field (cytofluorimetry) and in proteomic studies (bidimensional electrophoresis, mass spectrometry) with the aim of identify new biomarkers to place beside the traditional methods for the control of the animal origin food quality. From the results it’s possible to point out some relevant aspects from each experiment: 1. The cytofluorimetric techniques applied to O. edulis and C. gigas could bring to important developments in the search of alternative methods that quickly allows to identify with precision the origin of a specific sample, contributing to oppose possible alimentary frauds, in this case for example related to presence of a different species, also under a qualitative profile, but morpholgically similar. A concrete perspective for the application in the inspective field of this method has to be confirmed by further laboratory tests that take also in account in vivo experiments to evaluate the effect in the whole organism of the factors evaluated only on haemocytes in vitro. These elements suggest therefore the possibility to suit the cytofluorimetric methods for the study of animal organisms of food interest, still before these enter the phase of industrial working processes, giving useful information about the possible presence of contaminants sources that can induce an increase of the immune defence and an alteration of normal cellular parameter values. 2. C. gallina immune system has shown an interesting answer to benzo[a]pyrene (B[a]P) exposure, dose and time dependent, with a significant decrease of the expression and of the activity of one of the most important enzymes involved in the antioxidant defence in haemocytes and haemolymph. The data obtained are confirmed by several measurements of physiological parameters, that together with the decrease of the activity of 7-etossi-resourifine-O-deetilase (EROD linked to xenobiotic biotransformation processes) during exposure, underline the major effects of B[a]P action. The identification of basal levels of EROD supports the possible presence of CYP1A subfamily in the invertebrates, still today controversial, never identified previously in C. gallina and never isolated in the immune cells, as confirmed instead in this study with the identification of CYP1A-immunopositive protein (CYP1A-IPP). This protein could reveal a good biomarker at the base of a simple and quick method that could give clear information about specific pollutants presence, even at low concentrations in the environment where usually these organisms are fished before being commercialized. 3. In this experiment it has been evaluated the effect of the antibiotic chloramphenicol (CA) in an important species of commercial interest, Chamelea gallina. Chloramphenicol is a drug still used in some developing countries, also in veterinary field. Controls to evaluate its presence in the alimentary products of animal origin, can reveal ineffective whereas the concentration results to be below the limit of sensitivity of the instruments usually used in this type of analysis. Negative effects of CA towards the CYP1A- IPP proteins, underlined in this work, seem to be due to the attack of free radicals resultant from the action of the antibiotic. This brings to a meaningful alteration of the biotransformation mechanisms through the free radicals. It seems particularly interesting to pay attention to the narrow relationships in C. gallina, between SOD/CAT and CYP450 system, actively involved in detoxification mechanism, especially if compared with the few similar works today present about mollusc, a group that is composed by numerous species that enter in the food field and on which constant controls are necessary to evaluate in a rapid and effective way the presence of possible contaminations. 4. The investigations on fishes (Gadus morhua, and Salmo salar) and on a bivalve mollusc (Mytilus edulis) have allowed to evaluate different aspects related to the possibility to identify a biomarker for the evaluation of the health of organisms of food interest and consequently for the quality of the final product through 2DE methodologies. In the seafood field these techniques are currently used with a discreet success only for vertebrates (fishes), while in the study of the invertebrates (molluscs) there are a lot of difficulties. The results obtained in this work have underline several problems in the correct identification of the isolated proteins in animal organisms of which doesn’t currently exist a complete genomic sequence. This brings to attribute some identities on the base of the comparison with similar proteins in other animal groups, incurring in the possibility to obtain inaccurate data and above all discordant with those obtained on the same animals by other authors. Nevertheless the data obtained in this work after MALDI-ToF analysis, result however objective and the spectra collected could be again analyzed in the future after the update of genomic database related to the species studied. 4-A. The investigation about the presence of HSP70 isoforms directly induced by different phenomena of stress like B[a]P presence, has used bidimensional electrophoresis methods in C. gallina, that have allowed to isolate numerous protein on 2DE gels, allowing the collection of several spots currently in phase of analysis with MALDI-ToF-MS. The present preliminary work has allowed therefore to acquire and to improve important methodologies in the study of cellular parameters and in the proteomic field, that is not only revealed of great potentiality in the application in medical and veterinary field, but also in the field of the inspection of the foods with connections to the toxicology and the environmental pollution. Such study contributes therefore to the search of rapid and new methodologies, that can increase the inspective strategies, integrating themselves with those existing, but improving at the same time the general background of information related to the state of health of the considered animal organism, with the possibility, still hypothetical, to replace in particular cases the employment of the traditional techniques in the alimentary field.